A weight coefficient distribution method based on quantile impact value for modeling low calorific value in coal-fired power plants. Issue 2 (1st June 2023) - Qi, Minfang; Luo, Huageng; Fu, Zhongguang
ABSTRACT: In this paper, the quantile impact value (QIV) method was proposed as a weight coefficient distribution method to evaluate the influence of proximate analysis components on the low calorific value (LCV) of blended coals. Through data analysis technology, a new prediction model based on the QIV and the support vector regression (SVR) has been proposed to estimate the LCV. The comparisons between different analysis results reveal that the QIVW-GA-SVR model proposed here is consistently better than those models without weight coefficient distribution.